Центральна гемодинаміка і транспорт кисню у дітей з гнійно-запальною патологією, з урахуванням ролі еферентних методів детоксикації - Курочкін, Михайло Юрійович; Городкова, Юлія Вячеславівна; Давидова, Анна Григорівна (УМСА, 2015)
Вивчено особливостi впливу екстракорпоральної детоксикації (плазмаферез) на центральну гемодинаміку, кисневий режим в процесі інтенсивної терапії тяжких бактеріальних інфекцій у дітей, в тому числі у новонароджених. Дослiдження проведено у 26 новонароджених (з них у 6 дiтей застосовувався дискретний плазмаферез) i 31 дитини старшого віку (у 16 застосовувався дискретний плазмаферез). В ситуаціях, коли від терапії відсутній позитивний ефект, показане проведення дискретного плазмаферезу, ефективність якого підтверджується відновленням збалансованої тканинної доставки і поглинання кисню та нормодинамiї кровообiгу.
Abstract. The problem of purulent – inflammatory diseases in children and control of them is relevant for the health care system of the country due to severe endotoxemia, leading to the multiple organ failure and mortality. The aim of research. To identify the effect of extracorporeal detoxication (plasmapheresis) on central hemodynamics and oxygen regime in the intensive care of serious bacterial infections in children, including newborns. Materials and methods. The analysis of hemodynamics and oxygen regime was conducted in 66 children with bacterial infections (sepsis, community-acquired hard pneumonia, gangrenous-perforated appendicitis) who were treated at the intensive care unit (ICU) of Zaporizhzhia municipal multidisciplined children's hospital number 5 in the period from 2011 to 2015. The patients they were divided into 2 groups: the first group included 26 newborns, and in the second - 31 children older than a month. Each group was divided into two subgroups: in subgroup A (main) – discrete plasmapheresis was used with baseline intensive care, subgroup B (control) included children who received only basic intensive care. Basic therapy included: antibiotic therapy (empirical, based on the data of microbiological monitoring, clinical, epidemiological analysis and dynamic clinical - laboratory parameters), infusion detoxication therapy, respiratory therapy (oxygen therapy, mechanical ventilation), reologic correctors etc. Before plasmapheresis moderate hemodilution was performed by 7-10% of circulating blood volume. Results. Hemodynamic parameters in the first phase of group 1 A of infants characterized as circulations hyperdynamia – cardiac index (CI) was 4.55 L/min/m2, heart rate (HR) was 146,23 ± 11,98 bpm. The ratio between oxygen delivery and oxygen consumption – oxygen regime index (ORI) - was stressful - 2.46 conventional units (c.u.). After plasmapheresis there was a tendency to normalization of the ratio of oxygen delivery and consumption - ORI was 2.66 c.u. Moderate hyperdynamia of circulation remained. At the 6-7-th day hemodynamics and oxygen transport returned to middle-aged parameters, OMI was balanced. In the control group, hemodynamic and oxygen΄s transport approached to the referent. Central hemodynamic parameters of group 2 A and 2 B on admission were characterized as a moderate circulation hyperdynamia, ORI showed stressful oxygen mode. In the 2nd day hemodynamic situation was rated as expressed hyperdynamia in group 2 A and moderate circulation hyperdynamia with a tendency to normodynamia in the control group. After plasmapheresis the hemodynamics of patients in 2 A group were characterized by a tendency to lower heart rate and increasing of the arterial pressure, a significant decrease of CI - on 8,84% (p<0,05) without significant changes of SI, and ORI was 3.10 c.u. - that is balanced. On the 5th day in children of 2 A group hemodynamic profile was responsible for normodynamia circulation, ORI was balanced - 3.43 cu. On the 7th day of the research CI was decreased due to the reducing of the heart rate in 2 A group. In the patients of the 2 B groups CI matched middle-aged indicators, indicators of oxygen transport was balanced to the 5-th day, and in the 7th day the indices were at similar pattern – circulation normodynamia. Conclusions.1. In cases where the intensive care in children with purulent-inflammatory patology does not have positive effect (ORI becomes more intense) discrete plasmapheresis is recommended, as its effectiveness is confirmed by balance of oxygen transport. 2. Plasmapheresis in the stage of circulation hyperdynamia with preventive moderate hemodilution (called "venous backwater") helps to restore blood circulation to normodynamia. 3. In newborns and babies from control group who didn’t need plasmapheresis, ORI (ratio between oxygen delivery and oxygen consumption) was balanced (3-3,5 conventional units) all the days of study.
Keywords: бактерiальнi iнфекцiї; ендотоксемія; новонароджені; діти; гемодинаміка; плазмаферез